The Effectiveness of Mobile Phone Text Messages on the Adherence of Antiretroviral Drug Taking in Patients Living with HIV/AIDS: A Meta-Analysis - Fara Aristya Prisma; Hanung Prasetya; Burhannudin Ichsan (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The use of ARV therapy has been shown to reduce the mortality and morbidity of PLHIV. The characteristic factor of the PLHIV health care system is a key factor as well as how health workers and services synergize to improve patient adherence to adherence to taking ARVs. Subjects and Method: This research was conducted using a systematic review and meta-analysis with PICO namely, Population: PLHIV. Intervention; mobile phone text message. Comparison: not given a mobile phone text message. Outcome: obediently taking ARVs. By searching articles in 4 databases namely PubMed, Google Scholar, Science Direct, and ProQuest published from 2012 to 2022, entering the following keywords (“Mobile phone text messages” OR mHealth) AND antiretroviral AND (HIV or AIDS) AND “Randomized controlled trials”. Articles were selected using PRISMA flow and data analysis using the Review Manager 5.3 application. Results: There are a total of 9 articles using the RCT study design with a total sample of 2,762 PLHIV from China, Estonia, Nigeria, Cameroon, Kenya, and Mozambique which have been subject to systematic review and meta-analysis. The data that has been processed shows that mobile phone text messages are effective in increasing PLWHA adherence in taking ARVs, and are statistically close to significant. PLHIV who receive mobile phone text messages are more likely to comply with taking ARVs 1.12 times than those who do not receive mobile phone text messages (RR= 1.12; 95% CI= 1.00 to 1.26; p= 0.050). Conclusion: Mobile phone text messages are effective in increasing PLWHA compliance in taking ARVs. Keywords: HIV/AIDS, ODHA, ARV, mobile phone text messages. Correspondence: Fara Aristya Prisma, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java 57126. Email: fara.aristya@gmail.com. Mobile: +6285697129819.